Cellular and Molecular Mechanisms Underpinning Macrophage Activation during Remyelination - Lloyd, Amy F.; Miron, Veronique E. (Frontiers in Cell and Developmental Biology, 2016)
Remyelination is an example of central nervous system (CNS) regeneration, whereby myelin is restored around demyelinated axons, re-establishing saltatory conduction and trophic/ metabolic support. In progressive multiple sclerosis, remyelination is limited or fails altogether which is considered to contribute to axonal damage/ loss and consequent disability. Macrophages have critical roles in both CNS damage and regeneration, such as remyelination. This diverse range in functions reflects the ability of macrophages to acquire tissue microenvironment-specific activation states. This activation is dynamically regulated during efficient regeneration, with a switch from pro-inflammatory to inflammation-resolution/ pro-regenerative phenotypes. Although some molecules and pathways have been implicated in the dynamic activation of macrophages, such as NFκB, the cellular and molecular mechanisms underpinning plasticity of macrophage activation are unclear. Identifying mechanisms regulating macrophage activation to pro-regenerative phenotypes may lead to novel therapeutic strategies to promote remyelination in multiple sclerosis.